2020
DOI: 10.3390/vetsci7020049
|View full text |Cite
|
Sign up to set email alerts
|

HSF3 and Hsp70 Expression during Post-Hatch Cold Stress in Broiler Chickens Subjected to Embryonic Thermal Manipulation

Abstract: Decades of selective breeding for commercial purposes have rendered the broiler chicken (Gallus gallus domesticus) highly susceptible to heat and cold stress. A multitude of studies have documented the effects of thermal manipulation (TM) on broiler thermotolerance during periods of post-hatch heat stress, but very few have focused on the effect of TM on a broiler’s ability to withstand cold stress. Therefore, the primary objective of the current study is to determine the effects of TM on the acquisition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Intermittent manipulation in incubation temperature between different embryonic ages resulted in thermoregulatory functions being boosted; 3 h of 39.5°C/d from E16 to E18 [21], 39.5°C for 12 h/d at E7-E16 [15,16,24], and 60 minutes exposure to 15°C at E18-E19 [57]. In our review, the similar effect was confirmed by [49,50] at 38.5-39.5°C for 18 h/d from E10 to E18 and, David et al [18] at 39.5°C for 18 h/d from E7 to E16. It's clear that thermotolerance acquisition in broiler chickens can be enhanced by application of TM between E7 to E18, a period that is termed the critical stage and, the ideal embryonic age for TM.…”
Section: Thermal Manipulation and Thermotolerance Acquistionsupporting
confidence: 72%
See 2 more Smart Citations
“…Intermittent manipulation in incubation temperature between different embryonic ages resulted in thermoregulatory functions being boosted; 3 h of 39.5°C/d from E16 to E18 [21], 39.5°C for 12 h/d at E7-E16 [15,16,24], and 60 minutes exposure to 15°C at E18-E19 [57]. In our review, the similar effect was confirmed by [49,50] at 38.5-39.5°C for 18 h/d from E10 to E18 and, David et al [18] at 39.5°C for 18 h/d from E7 to E16. It's clear that thermotolerance acquisition in broiler chickens can be enhanced by application of TM between E7 to E18, a period that is termed the critical stage and, the ideal embryonic age for TM.…”
Section: Thermal Manipulation and Thermotolerance Acquistionsupporting
confidence: 72%
“…Among the 24 intermittent TM studies, 20 articles reported the TM effect on hatchability, of which 65% found no significant effect, 30% being reduced, and a comparative study by Dalab and Ali [46] reported increased and decreased hatchability at different embryonic age. Meanwhile, embryo and/or hatch weight and chick quality were reported in 18 articles, of which 12 (67%) found no significant effect, three studies reported increased [2,38,50], and three reported reduced effect of TM on embryo and/or hatch weight and chick quality [42,45,46].…”
Section: Search Strategy and Selection Of Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was shown that chicks subjected to TM resulted had decreased HSF1 , HSF3 , and HSP70 expression in the jejunal mucosa after 7 days of HS exposure in comparison with chicks incubated under standard conditions [ 40 ]. Furthermore, CS was reported to induce the expression of HSF3 and HSP70 in the liver and spleen of broiler chickens after 5 days of exposure to CS, but TM mitigated this response [ 84 ]. During thermal stress, the decreased expression of heat shock proteins in TM chicks compared to controls suggests that TM chicks were less susceptible to thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and his colleagues [11] found that the level of HSP70 declined in the heart 6 hours after the heat stress, but the HSF3 expression remained high. Tarkhan and his colleagues [49] examined the HSP70 and HSF3 expression levels in cold stress. They found decreased expression levels in the liver in case of both genes.…”
Section: Discussionmentioning
confidence: 99%